Means, ends and the ethics of fear-based public health campaigns. Issue 6 (13th May 2016) - Bayer, Ronald; Fairchild, Amy L
Abstract : Controversy has swirled over the past three decades about the ethics of fear-based public health campaigns. The HIV/AIDS epidemic provided a context in which advocacy groups were almost uniformly hostile to any use of fear, arguing that it was inherently stigmatising and always backfired. Although this argument was often accepted within public health circles, surprisingly, the bioethicists who first grappled with this issue in terms of autonomy and coercion in the 1980s were not single-minded: fear could be autonomy-enhancing. But by the turn of the 21st century, as opponents of fear-based appeals linked them to stigmatisation, ethicists typically rejected fear as inherently unethical. The evidence has increasingly suggested that fear-based campaigns 'work.' Emotionally charged public health messages have, as a consequence, become more commonplace. We conclude that an ethics of public health, which prioritises population well-being, as contrasted with the contemporary focus of bioethics on autonomy, provides a moral warrant for ensuring that populations understand health risk 'in their guts.' This, we argue, does not relieve public health authorities from considering the burdens their efforts may impose on vulnerable populations.